Kritik – Selbstaffirmation – Othering: Immanuel Kants Denken der Zweckmässigkeit und die koloniale Episteme - Hostettler, Karin (transcript, 2020)
An interpretation of Immanuel Kant's philosophy, which shows the self-location of critical philosophy as caught in a colonial episteme.